IMPLEMENTATION OF HUMAN RESOURCE MANAGEMENT BASED ON ISLAMIC VALUES AT PT BANK SUMUT SYARIAH BRANCH PADANGSIDIMPUAN - Nursaima Harahap (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to determine the impact or effect of human resource management based on Islamic values on PT Bank Sumut Cabang Syariah Padangsidimpuan. This research is descriptive qualitative research. The subjects of this study were branch leaders, deputy branch leaders, and 10 employees of PT Bank Sumut Cabang Syariah Padangsidimpuan. Data collection techniques are obtained from observations, interviews, and documentation. And the data processing and analysis techniques are using data reduction, data display, and conclusions. Based on the results of research conducted by researchers, human resource management based on Islamic values at PT Bank Sumut Syariah Branch Padangsidimpuan is in accordance with Islamic values, which include creed values, sharia values, and moral values. The impact or effect after the implementation of human resource management in accordance with Islamic values is found in the company's work culture, human resource management processes, and employee productivity and bonafficity.Keywords: Implications, Human Resource Management, Islamic Values